The Skill of the Organizer in Formal and Informal Events: Etiquette and Behavior Culture During Event Management - Karimjonova Shahlo Ravshanjonovna (PT FORMOSA CENDEKIA GLOBAL, 2024)
Effective event management requires a deep understanding of the skills necessary for organizing both formal and informal events. This paper examines the critical role of the organizer, focusing on the importance of etiquette and behavior culture in ensuring successful event outcomes. By analyzing various event management scenarios, the study highlights key competencies, including communication, adaptability, and cultural awareness, essential for navigating the complexities of event planning and execution